Dimension of Governance on Microfinance Institutions in South Asian Countries (A Cross Country Study of Nepal and Bangladesh) - Lamichhane, Basu Dev; Bhaumik, Amiya; Gnawali, Achyut (Janabhawana Research Journal, 2023)
This research aims to empower Nepalese and Bangladeshi microfinance institutions (MFIs) to strengthen their microfinance governance. By contrasting the governance structures of MFIs in Bangladesh and Nepal, the study focuses on the corporate governance aspect of MFIs for sustainability. This study adopted an interpretive methodology and a qualitative research design. Internal control, timely internal audit, proper rules and regulations, institutional culture, full compliance with rules and regulations, budget and annual plan review, financial transparency, and board literacy education are the main dimension of corporate governance, broadly influencing MFIs for sustainability. The study found sustainability of MFIs is affected by proper guidelines for operation, effective internal control mechanisms, professional management, board literacy education, financial transparency, the rule of law in operation, institutional culture, and review of budget and achievement. The findings of the study might be applicable to the BFIs, MFIs, regulatory authorities, economist, HR analyst, and planners.